2014
DOI: 10.1073/pnas.1413550111
|View full text |Cite
|
Sign up to set email alerts
|

Antibody persistence and T-cell balance: Two key factors confronting HIV vaccine development

Abstract: The quest for a prophylactic AIDS vaccine is ongoing, but it is now clear that the successful vaccine must elicit protective antibody responses. Accordingly, intense efforts are underway to identify immunogens that elicit these responses. Regardless of the mechanism of antibodymediated protection, be it neutralization, Fc-mediated effector function, or both, antibody persistence and appropriate T-cell help are significant problems confronting the development of a successful AIDS vaccine. Here, we discuss the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
85
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 107 publications
(176 reference statements)
4
85
0
Order By: Relevance
“…It has been reported that increased CD40 stimulation, either by an anti-CD40 Ab or by transgenic CD40L overexpression, augments early Ab responses but significantly reduces their t 1/2 due to premature germinal center regression (54,55). In line with these observations is the remarkably short lifespan of Env-specific Abs induced by vaccination (56)(57)(58).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It has been reported that increased CD40 stimulation, either by an anti-CD40 Ab or by transgenic CD40L overexpression, augments early Ab responses but significantly reduces their t 1/2 due to premature germinal center regression (54,55). In line with these observations is the remarkably short lifespan of Env-specific Abs induced by vaccination (56)(57)(58).…”
Section: Discussionmentioning
confidence: 74%
“…Again, the similarities in Gag-specific CD4 + T cell responses of mice and human vaccinees suggest that the ISH approach may be applicable to humans, as well. Whether this approach can be extended to Th cells with non-HIV specificities needs to be explored, but the idea to avoid possibly detrimental HIV-1-specific CD4 + T cell responses is appealing (58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the immune correlates of protection against HIV/SIV continues to be a central pursuit for the vaccine research community (29)(30)(31). Multiple vaccine studies in NHPs and humans have implied that functional antibody responses against Env are necessary for protective immunity (3,18,32).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to consider that vaccination itself may alter the mucosal environment such that transmission is favored over protection (31,36,37). This could result from the generation and homing of vaccine-elicited CD4+ T cells to the portal of entry, which in turn mitigates the beneficial effects of the vaccine-elicited humoral immune response (38-40).…”
Section: Discussionmentioning
confidence: 99%
“…They have done important work, and written thoughtfully and provocatively about this topic [3]. We share their view that durability of the vaccine-induced antibody response is a key issue and must be addressed as part of the community-wide effort to discover and develop an HIV vaccine that induces protective antibodies and which is practical and affordable for use globally.…”
mentioning
confidence: 99%